2010
DOI: 10.2353/ajpath.2010.100087
|View full text |Cite
|
Sign up to set email alerts
|

Early Oligodendrocyte/Myelin Pathology in Alzheimer's Disease Mice Constitutes a Novel Therapeutic Target

Abstract: The detection of myelin disruptions in Alzheimer's disease (AD)-affected brain raises the possibility that oligodendrocytes undergo pathophysiological assault over the protracted course of this neurodegenerative disease. Oligodendrocyte compromise arising from direct toxic effects imparted by pathological amyloid-␤ peptides and/or through signals derived from degenerating neurons could play an important role in the disease process. We previously demonstrated that 3؋Tg-AD mice, which harbor the human amyloid pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
173
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(195 citation statements)
references
References 49 publications
10
173
1
1
Order By: Relevance
“…23 Animal models have shown increased amyloid deposition after stroke, and white matter injury may predispose to the neurodegenerative effects of A␤. 9 Although the neurovascular hypotheses concerning A␤ clearance seem plausible, 24 little evidence from human studies suggests that vascular risks are also amyloidogenic. 25 Even though amyloid deposition can be enhanced by circulatory defects, vascular effects may be easily overwhelmed once AD pathology becomes advanced.…”
Section: 19 -21mentioning
confidence: 99%
See 1 more Smart Citation
“…23 Animal models have shown increased amyloid deposition after stroke, and white matter injury may predispose to the neurodegenerative effects of A␤. 9 Although the neurovascular hypotheses concerning A␤ clearance seem plausible, 24 little evidence from human studies suggests that vascular risks are also amyloidogenic. 25 Even though amyloid deposition can be enhanced by circulatory defects, vascular effects may be easily overwhelmed once AD pathology becomes advanced.…”
Section: 19 -21mentioning
confidence: 99%
“…9 Brain microinfarcts may cause cognitive impairment via reduction of brain reserve, but the mechanism appears to be independent of typical AD lesions. 10 A recent study from the Alzheimer's Disease Neuroimaging Initiative (ADNI) has shown that the longitudinal changes in CSF A␤ 42 , [ 18 F]fluorodeoxyglucose (FDG) PET uptake, and MRI hippocampal volume are reflective of AD progression after cerebral amyloid deposition.…”
mentioning
confidence: 99%
“…38 Impaired myelinated axons have been detected in the brains of Alzheimer disease patients and been supposed as an early component of Alzheimer disease. [1][2][3]39,40 Abnormalities in CNS myelination affect the molecular organization at and around nodal axons leading to disturbances in CNS functions. For example, the heterozygous proteolipid protein transgenic mice exhibited profound reduction in Nav1.6 clusters, loss of the paranodal axo-glial apparatus, and a marked increase in Nav1.2.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the vulnerability of oligodendrocytes to hypoperfusion, oxygen radicals, products of activated microglia, and other toxic insults or the alterations in cholesterol turnover and trafficking within the brain as a result of myelin injury and repair could be important determinants in AD pathology [77]. Similarly, A 42-induced caspase activation and apoptosis in mouse oligodendrocyte precursor cell line are crucial evidence linking myelin disruption with AD pathology [78]. The role of leptin in regulating myelin synthesis during brain development has been indicated in several studies over the years.…”
Section: Effects Of Leptin On Myelination: the Ad Connectionmentioning
confidence: 99%